PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP GROWTH MINDSET DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS V SD SAINS ISLAM AL-FARABI - Sudrajat; Yuli Yani; Yusliyan B; Yenti Apriyani; Zakia Eka Putri; Agus Irfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of using Wordwall learning media on the growth mindset of fifth-grade students in mathematics learning on the topic of perimeter and area of plane figures at SD Sains Islam Al-Farabi. The research employed a quantitative approach using a quasi-experimental method with a One Group Pretest-Posttest Design. The subjects of the study consisted of 28 fifth-grade elementary school students selected using saturated sampling techniques. Data were collected through growth mindset questionnaires, observation, and documentation. The instrument used was a Likert-scale questionnaire based on growth mindset indicators developed from Carol S. Dweck’s theory. Data analysis techniques included normality tests, homogeneity tests, and paired sample t-tests. The results showed that the average pretest score of students’ growth mindset was 74.79, while the posttest average score increased to 84.71. The normality test results indicated that the data were normally distributed, and the homogeneity test showed homogeneous data variance. The paired sample t-test analysis obtained a significance value of 0.000 < 0.05, indicating a significant effect of using Wordwall learning media on students’ growth mindset. In addition, the N-Gain test result of 0.71 was categorized as high, indicating that Wordwall was effective in improving students’ growth mindset. Therefore, Wordwall learning media can be used as an innovative and interactive learning alternative to foster students’ positive mindsets in mathematics learning.